2019
DOI: 10.3389/fped.2019.00340
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Endothelium in Neonatal Sepsis: Basic Mechanisms and Translational Opportunities

Abstract: Neonatal sepsis remains a major health issue worldwide, especially for low-birth weight and premature infants, with a high risk of death and devastating sequelae. Apart from antibiotics and supportive care, there is an unmet need for adjunctive treatments to improve the outcomes of neonatal sepsis. Strong and long-standing research on adult patients has shown that vascular endothelium is a key player in the pathophysiology of sepsis and sepsis-associated organ failure, through a direct interaction with pathoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 183 publications
0
32
0
1
Order By: Relevance
“…During sepsis, the difference between neonates, children, and adults have also been described at the level of endothelium and interaction between pathogen and immune system (28). Differently from adults, neonates have reduced recruitment of polymorphonucleate cells (PMN) to the site of infection, diminished phagocytic activity, and intracellular killing by reactive oxygen radicals, and a higher pathogen load per ml of blood as part as a "microbe-tolerant" strategy (29,30).…”
Section: Neonatal Cardiovascular Physiology Vs Children and Adolescentsmentioning
confidence: 99%
“…During sepsis, the difference between neonates, children, and adults have also been described at the level of endothelium and interaction between pathogen and immune system (28). Differently from adults, neonates have reduced recruitment of polymorphonucleate cells (PMN) to the site of infection, diminished phagocytic activity, and intracellular killing by reactive oxygen radicals, and a higher pathogen load per ml of blood as part as a "microbe-tolerant" strategy (29,30).…”
Section: Neonatal Cardiovascular Physiology Vs Children and Adolescentsmentioning
confidence: 99%
“…This enables reason to conceptualize the role of periodontal infection process in abstraction from the restriction of limited confined infection as the condition of its ability of sustaining a low-grade systemic inflammatory status [24]. The construction of this theory and expansion of the role of peripheral inflammation has posed essential questions for analysis of the dysregulation of oral microbiome [25], [26]. Therefore, the potential damaging effect of periodontal pathogens in pregnant women is its tendency to cause low-grade systemic inflammation, which may lead to premature rupture of membranes [18].…”
Section: Periodontal Disease and Oral Microbiomementioning
confidence: 99%
“…Whether the impact from periodontal infection influences or explicates a direct effect is uncertain but suggests a potentially damaging interaction between periodontitis and preterm delivery (PTD) [23]. From the empirical findings, a clear interest focused on the placental inflammation has emerged [1], [4], [25], [26], [27], [28], [29]. Central relationship between the periodontal disease and preterm birth (PTB) is due to an inflammatory response system responding to signal from bacterial invasion [30], [31].…”
Section: Periodontal Disease and Oral Microbiomementioning
confidence: 99%
See 1 more Smart Citation
“…Adult sepsis has been studied in depth, but many abundant studies stated that the neonatal immune response to sepsis is different from adults; comparable research on neonatal vascular endothelium is not enough. Neonatal endothelial cells expressing lower amounts of adhesion molecules show a reduced capacity to reactive oxygen species [3]. In the past decades, emerging studies showed activation of lymphocytes, neutrophils, and mononuclear macrophages played crucial roles in the progression of neonatal sepsis.…”
Section: Introductionmentioning
confidence: 99%